A small scale Pressure Retarded Osmosis power plant: dynamics of the brackish effluent discharge along the coast. (15th January 2017) - Stancanelli, Laura Maria; Musumeci, Rosaria Ester; Cavallaro, Luca; Foti, Enrico
Abstract: The feasibility of a small scale Pressure Retarded Osmosis (PRO) plant located along the eastern coast of Sicily (Italy) is assessed by considering fresh water intake from a river and salt water intake from the sea. Firstly, PRO design methods are applied in order to estimate potential power production in terms of both the availability of water resources and of local salinity gradients. Secondly, the discharge dynamics of the brackish plant effluent in the coastal waters is investigated using an hydrodynamic model, taking into account wave - current interaction close to the river mouth. The results of the numerical simulations allow to identify the area affected by the brackish discharge, as a function of the nearshore wave climate conditions. Results show that the plume propagation is mainly controlled by the wave direction, whereas significant wave height and peak wave period have a minor influence. Plume hydrodynamics analysis is useful in optimizing the layout of the PRO plant in terms of the placement of the sea water intake and the effluent discharge, both of which should be properly located outside the surf-zone. Plume hydrodynamics analysis is also important for the evaluation of PRO plant impacts on the coastal saline concentration which may affect the local ecosystems. Abstract : Highlights: The feasibility of a small scale PRO plant is studied at a river mouth. We assess potential plant power considering local river-sea resources. Nearshore flow strongly influences the brackish effluent dynamics. Intake/outfall locations are optimized accounting for plume dynamics.